The Development of ESP Media Through Interactive HOTS e-Book Based on Local Wisdom in West Sulawesi - Kurnia Kurnia; Salasiah A; Areski Wahid; Muh. Rezky Naim; Abdul Wahab (Yayasan Adra Karima Hubbi, 2024)
Background. The urgency of this research is developing an interactive media HOTS e-book based on the local wisdom in West Sulawesi. It is collaborative and participatory of interactive media HOTS e-book will improve interest in learning and motivate ESP students to master English skills. Purpose. The purpose of this research is to improve English language skills students orally and in writing, develop learning media with Higher Order Thinking Skill (HOTS) combined with local knowledge of West Sulawesi. Method. The method of R&D was applied by using the DDDE (Decide, Design, Develop, and Evaluate) model which was chosen to develop this HOTS interactive e-book for ESP learners based on local wisdom at West Sulawesi. The small-scale trial of the HOTS E-book was carried out by experts of teacher, lecturers and also a large-scale trial was carried out by 46 students. The test subject was determined using the purposive sampling technique. The collecting research is carried out by providing questionnaire tests that have been collected descriptively. Results. Results shows that the ESP interactive HOTS e-book based on local wisdom, developed using the DDD-E model, meets the validity criteria with an average score of 3.89, is deemed practical with an average score of 3.67, and shows the effectiveness with 86.8% from the score test results of the ESP students at Unimaju. Conclusion. The ESP interactive HOTS e-book based on local wisdom in West Sulawesi, developed using the DDD-E model, is valid, practical, and effective. It equips lecturers and other educators with innovative tools to enhance critical literacy and critical thinking and promoting better learning outcomes for the local culture of West Sulawesi.